The Objectives of Secular Education - Jovaiša, Leonas (Acta Paedagogica Vilnensia, 1991)
Following the failure of educational goals based on Marxist ideology, mostly oriented to the needs of the economy, one of the biggest challenges faced by the schools of independent Lithuania is the search for educational objectives. The main guidelines of the educational goals should be a human being and the treatment of human nature, human interaction with the empirical values of the environment, and human interaction with ideal and spiritual values. However, in order to avoid unilateral educational objectives should be derived not only from the conception of human personality, not only from the sociological doctrines or philosophy of culture, not only from religious or atheistic interests, but from a holistic approach to reality and the process of education. The overall objective of education can be defined as follows: to help a human being in the development of the whole of the natural data on the basis of real and ideal values, and to be able to act wisely, creatively and act honestly in own life. In terms of goals, the word "help" is to be especially emphasized. Helping the student should change the now entrenched commanding. Teacher helping a student should set goals for himself, reflect on how to achieve them, and take practical action.